Housing Prices, Airport Noise and an Unforeseeable Event of Silence - Philipp Breidenbach; Patrick Thiel (RWI - Leibniz-Institut für Wirtschaftsforschung, 2023)
To evaluate the causal impact of noise exposure on housing prices, we exploit a sudden and massive reduction in flight traffic that occurred with the onset of the Covid-19 measures in Germany. Comparing locations differently exposed to pre-pandemic noise with a differencein-difference approach, we detect a 2.3% increase in prices for apartments that experienced a noise reduction. Disentangling temporal dynamics, we find a peak effect in mid-2021 (up to 6%), which does not yet allow a statement on whether effects remain persistently. In contrast to most evaluations showing that the erection of a disamenity affects prices negatively, we show that lifting the burden enables neighborhoods to catch up again immediately. The immediate catch-up contradicts a stickiness of housing prices regarding (temporal) local factors. The temporal pattern shows a clear peak of the effects during the pandemic, which potentially hints at information asymmetries since buyers may not know the non-pandemic noise level during the pandemic.
Keywords: O18; Q53; 330; Covid pandemic; aircraft noise; housing prices; hedonic function